Empiric antibiotic therapy resistance and mortality in emergency department patients with bloodstream infection: a retrospective cohort study - Leonhard M. von Beck; Gabriella Anna Rapszky; Veronika E. Kiss; Szilard Sandor; Szabolcs Gaal-Marschal; Tamas Berenyi; Csaba Varga; Bank G. Fenyves (BMC Emergency Medicine)
Abstract Background Timely management of sepsis in the emergency department, including the use of appropriate antimicrobials, is crucial for improving patient outcomes. Inadequate empiric antimicrobial treatment is associated with potential changes in patient outcomes. We aimed to pinpoint risk factors, characterize antibiotic resistance trends, and investigate the association between antibiotic resistance and mortality among patients with bacteremia admitted to the emergency department. Methods We conducted a retrospective analysis of emergency department patients admitted between 15/06/2016 and 30/09/2022. Patients with a positive blood culture receiving emergency department-initiated antibiotic therapy were included. Antibiotic administration, resistance, and survival data were collected. Descriptive statistics, survival analysis, and Cox proportional hazards models were performed. Results Of 157,884 emergency department visits, 1,136 patients had a positive blood culture and received antibiotic therapy initiated in the emergency department. Resistance against empiric antibiotics was 14.5%. The overall 30-day and one-year mortality was 38.6% and 61.8%, respectively. In adjusted Cox models, patients with Escherichia coli or Staphylococcus aureus infection had 36% lower and 44% higher risk of death, respectively. Although resistance to emergency department-administered antibiotic therapy was not associated with overall mortality, one-year mortality of patients with Escherichia coli bacteremia was higher in those with antibiotic resistance (69.0% vs. 49.4%, p = 0.011); these patients had a 1.5-fold increased risk of death in an adjusted Cox model. Conclusion The mortality of patients with bloodstream infection is high. The association of mortality with empiric emergency department-initiated antibiotic adequacy is pathogen-dependent.